Penerapan Model Pembelajaran Kooperatif Tipe Think-Pair-Share Untuk Meningkatkan Pemahaman Siswa Tentang Shalat Sunnah - Wahyu Hidayat (UMSU, 2021)
Cooperative learning model Think Pair Share is a process of learning activities that includes providing material, group division, giving questions, giving questions and delivering the results of group discussions conducted by students. Cooperative Think Pair Share type centers on students so that students play an active role and are directly involved in the learning process. This research process was carried out because of the learning process which was still classified as classic and less effective. In addition, the role of students is still not maximized then the learning process which takes place in the morning and afternoon today makes students bored and bored with the subject matter. This is the lack of understanding of students about prayer, especially Sunnah prayer and lack of interest, enthusiasm and learning outcomes of students in the learning process in Islamic Education subjects. This study aims to improve students' understanding of Sunnah prayer in Islamic Education subjects by applying the Think Pair Share Type Cooperative learning model in class VIII.3 SMP Negeri 2 Mattirobulu, Pinrang. The variable that becomes the target of change in this study is the result of increasing student understanding, while the action variable used in this study is the Think Pair Share Type Cooperative learning model. This type of research is a classroom action research conducted in 2 cycles, each cycle consisting of four stages, namely planning, acting, observing, and reflecting. The data collection techniques used was observation, interviews, tests and documentation. The data analysis techniques used were quantitative and qualitative descriptive analysis techniques. The results showed that the learning outcomes of students from cycle I to cycle II had increased. Thus, it can be concluded that the application of the Think Pair Share Type Cooperative learning model can improve the results of students' understanding of Sunnah prayer at SMP Negeri 2 Mattirobulu, Pinrang.